Leveraging Innovation, Data and Mapping for Healthier Soils - CIFOR-ICRAF; AICCRA; CA4SH (2025)
This presentation was given at the Global Climate-Smart Agriculture Conference from the 5-7 November 2025 in Brazil. The event brought together scientists, policymakers, investors and businesses to shape the future of food and agriculture ahead of the 30th Conference of the Parties (COP30) to the United Nations Framework Convention (UNFCCC). The presentation contributed to the thematic area on Plant Nutrition and Soil Health. It emphasises that healthy soils are foundational to climate adaptation, mitigation, biodiversity, and nutrition outcomes, yet scaling soil-improving practices requires context-specific strategies and better decision support. The session showcases emerging innovations in soil data generation, mapping, and interoperability, including digital public goods which aim to make soil information more accessible and actionable for farmers, policymakers, and value chain actors. AICCRA supported the Center for International Forestry Research and World Agroforestry (CIFOR-ICRAF) and the Coalition of Action 4 Soil Health (CA4SH) with the section on 'bridging soil health evidence and practice' - connecting scientific evidence on soil health with practical application and highlighting the importance of monitoring.